Screening of Infant-derived Lactobacillus rhamnosus and Its Promotion of Intestinal Organoid Growth - Sailun GAI; Xiaojie CHEN; Tao LING; Tengxun ZHANG; Meng GENG; Wei QI; Xuegang LUO; Tongcun ZHANG; Nan WANG (Shipin gongye ke-ji, 2022)
In this study, five strains of Lactobacillus rhamnosus (L. rhamnosus) and two strains of Lactobacillus paracasei (L. paracasei) isolated from infants were used as experimental bacteria and Lactobacillus rhamnosus GG as control strain. The gastrointestinal tolerance of these strains were evaluated through acid resistance test, bile salt resistance test, hydrophobicity test, automatic aggregation ability test and cell adhesion test. L. rhamnosus SW-02, the best effective strain in tolerance evaluation, was co-cultured with intestinal organoids. The morphology and growth status of organoids were observed by inverted phase contrast microscope, and the budding rate was calculated. The proliferation status of organoids was evaluated by EdU staining. The mRNA levels of the proliferation marker Ki67, intestinal stem cell marker Lgr5 and tight junction protein Zo-1 were measured by real-time PCR. The level of MUC2 was detected by enzyme-linked immunosorbent assay. The results showed that compared with other strains, L. rhamnosus SW-02 had strong acid resistance. SW-02, SW-03 and SW-X had strong bile salt resistance. LGG, SW-01, SW-02, SW-04 and TX-02 had high hydrophobicity to xylene. For automatic aggregation capability, SW-01 was the strongest, followed by SW-02. The adhesion test of HT-29 cells showed that SW-01, SW-02 and SW-03 had high adhesion ability. When SW-02 was co-cultured with intestinal organoids, SW-02 significantly (P<0.05) increased the budding rate and number of organoids, and promoted the growth of organoids. Compared with the control group, the mRNA levels of Ki67, Lgr5 and Zo-1 in SW-02 group were significantly increased, and the secretion of MUC2 was significantly increased (P<0.05). In conclusion, L. rhamnosus SW-02 has good gastrointestinal tolerance and the ability to promote the growth of intestinal organs, and can be used as a potential strain for the development of probiotic products in the future.